Autosomal dominant late onset cerebellar ataxia with myoclonus, peripheral neuropathy and sensorineural deafness: a clinicopathological report. Issue 1 (January 1984) - Baraitser, M; Gooddy, W; Halliday, A M; Harding, A E; Rudge, P; Scaravilli, F
Abstract : Three members of a family were affected by an autosomal dominant disorder comprising cerebellar ataxia, sensorineural deafness, myoclonus, and peripheral neuropathy. This is the second kindred with this syndrome reported to date. Necropsy of the proband showed loss of cells in the dentate nuclei, a reduced amount of cerebellar white matter, and pallor of the gracile tracts in the spinal cord.